Graf Nilpoten Dari Gelanggang Bilangan Bulat Modulo Berorde Pangkat Prima - Malik, Deny Putra; Wardhana, I Gede Adhitya Wisnu; Dewi, Putu Kartika; Widiastuti, Ratna Sari; Maulana, Fariz; Syarifudin, Abdul Gazir; Awanis, Zata Yumni (Prodi Pendidikan Matematika Universitas Pesantren Tinggi Darul Ulum Jombang, 2023)
Nilpotent graph of ring integer modulo is one of the graph representations in algebraic structures. This study aims to find out the shape and properties of a nilpotent graph of ring prime numbers modulo which is then generalized to a ring of integers modulo with arbitrary prime power. The method used in this research is a literature study. In the ring of integer modulo, we get the shape of a nilpotent graph as a star graph. Then, the characteristic of a nilpotent graph on a ring integer modulo with arbitrary prime power is that it contains a complete subgraph and contains a number of as a star subgraph.